Gambaran Kecacingan Soil Transmitted Helminth (STH) Pada Kuku Perajin Batu Bata - Sri Idayani; Ni Luh Nova Dilisca Dwi Putri (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background of Study: Worms are one type of infectious disease caused by parasitic animals, namely worms. Polluted soil is the cause of the transfer of worm eggs from the soil into the human body through hands or nails containing worm eggs, then the eggs enter the mouth with food. This condition often occurs in children who often play on the ground as well as in adults who work in the garden or in the fields. This study aims to determine the description of worms in brick craftsmen.Methods: This research is a descriptive type with 30 respondents. The sampling technique used was purposive sampling. Worm data was obtained by interviewing about personal hygiene and personal protective equipment as well as examining worm eggs on the nails of brick craftsmen. The results of the questionnaire and examination of worm eggs were analyzed descriptively.Results: The results showed that there was no infection with Soil Transmitted Helminths worms in brick craftsmen in X Village, Jembrana Regency. Most of the brick craftsmen already have personal hygiene in the good and sufficient category. These results are reinforced by the results of interviews about personal hygiene and personal protective equipment which includes nail hygiene, hand washing habits, the habit of using footwear and gloves.Conclusion: It is hoped that brick craftsmen will further increase awareness of maintaining personal hygiene and using Personal Protective Equipment while working so that they can prevent the danger of infection with Soil Transmitted Helminth worm eggs.Keywords: Nails; Soil Transmitted Helminths; Bricks crafters